Foreign Investment in Local Currency Bonds : Considerations for Emerging Market Public Debt Managers - Sienaert, Alex (World Bank, Washington, DC, 2013)
Foreign investors are increasingly important participants in the local currency sovereign bond markets of developing countries. This note provides context on the overall growth of local currency sovereign debt markets in emerging markets and the growth of foreign investor participation in these markets, a short review of the relevant academic literature, and a summary of the sources of foreign demand. The note concludes with a discussion of the implications of growing foreign investor participation for the managers of public domestic debt in developing countries. The aim of the note is to provide a useful, practically-oriented primer for debt managers beginning to engage on this issue, and in particular to facilitate moving the dialogue beyond overly simple categorizations of countries as "emerging markets" and of investors as a homogeneous source of "hot money".